(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Mathematics is one of the major subjects where in, it is not easily to understand and we need more time and effort to learned with this subject According to Mahanta, (2019) and Calculus “is one of the oldest subjects in mathematics, and it is very much alive and still evolving. Besides its mathematical importance and its links to other branches of mathematics, such as geometry or differential equations, it is widely used in physics, engineering, economics, and biology” According to Bernard Dacorogna, (2014). The COVID19 pandemic has created additional learning pressure from virtual math lessons. In this pandemic, the school adapted to distance learning for students. Online classes are one of the new normal educations set up according to Bringula, 2021. The researchers utilized the descriptive method in determining the Students Perception in Solving Abilities in Calculus during New Normal. Purposive Sampling is used in determining the respondents from the different sections of 3rd year and 4th year level, 20 respondents per year level, for a total of 40 respondents. The results of this study showed that calculus students had high solving ability even when conducted in an online learning modality. They can answer learning management systems, achieve passing scores on major exams, and even recite and participate in online discussion and with the help of parents, school, and professors. Online learning helps students work efficiently solve calculus skills with the help of parents, professor, and school. Despite the factors that influence to learn. The results of this study will be used to identify factors. It can affect student learning. To find solutions to some of the problems encountered by students. The main aim is to improve solving skills through online modalities and find ways to reduce the problems that can arise in calculus discussions.